2017
DOI: 10.1080/23311886.2017.1302785
|View full text |Cite
|
Sign up to set email alerts
|

Health information seeking in the digital age: An analysis of health information seeking behavior among US adults

Abstract: Background: Given the increasing availability of internet, it has become a common source of health information for all population including students. However, the actual effect of this increased access to information on the health status and its different aspects needs to be studied more. This study aimed to investigate the correlations between online health information seeking behavior and health related quality of life in a sample of high school students of Iran. Methods: A survey was conducted among seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
363
5
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 462 publications
(436 citation statements)
references
References 28 publications
27
363
5
10
Order By: Relevance
“…The advent of the digital era has radically changed the way individuals search for information and this is particularly relevant for health-related information [1]. A 2013 study [2] found that 59% of U.S. adults had looked for health information on the Web in the previous year and that about one in three U.S. adults use the Internet to figure out what medical condition they have.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of the digital era has radically changed the way individuals search for information and this is particularly relevant for health-related information [1]. A 2013 study [2] found that 59% of U.S. adults had looked for health information on the Web in the previous year and that about one in three U.S. adults use the Internet to figure out what medical condition they have.…”
Section: Introductionmentioning
confidence: 99%
“…The Internet has changed the ways in which people search for health information. Some studies have shown that 177 million Americans use social media platforms and Internet queries to determine their medical condition or that of others (Casey, ; Jacobs, Amuta & Jeon, ). Recently, social media and other Web based data sources have been used to spread awareness on the outbreak of diseases (Brownstein, Freifeld, Reis & Mandl, ; Paul & Drezde, ; Signorini, Segre & Polgreen, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a large survey of California residents, (Nguyen, Mosadeghi, & Almario, 2017) found evidence of digital disparities in online health information seeking: Elderly, racial/ethnic minority, non-English speaking, and less educated individuals were less likely to ever use the Internet or to engage in online health information seeking. Inequalities in health information seeking have also been documented by others showing that that younger people, those with higher socioeconomic status, higher level of education, and higher Internet skills are more likely to report the use of online sources for health information (Jacobs, Amuto, & Jeon, 2017). In addition to limited Internet access, socioeconomically disadvantaged populations seeking online health information experience other barriers to information gathering such as connectivity problems and frustration during health information searches (McCloud, Okechukwu, Sorensen, & Viswanath, 2016).…”
Section: Introductionmentioning
confidence: 81%